An exploratory survey of green supply chain management in Chinese manufacturing small and medium-sized enterprises. Issue 1 (2nd February 2015) - Huang, Xiangmeng; Tan, Boon Leing; Ding, Xiaoming
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to empirically investigate the pressures and drivers that have been experienced by Chinese manufacturing small and medium enterprises (SMEs) in terms of green supply chain management (GSCM). Design/methodology/approach – The research framework and hypotheses are examined by a questionnaire survey through e-mails conducted in China in 2011. The empirical analysis is based on the data from 202 SME manufacturers in China. Validity and reliability of the items employed in the research is assessed through Cronbach's α test. Hypotheses for the identification of GSCM pressures and drivers to SMEs as well as the differences that exist among different industrial sectors are tested by adopting descriptive statistics analysis and analysis of variance test. Findings – This study finds that Chinese manufacturing SMEs have been under pressures from a variety of sources, including regulations, customers, suppliers and public awareness in terms of GSCM. Besides, internal drivers are also an important encouragement for SMEs to consider GSCM. Moreover, Chinese manufacturing SMEs from different industrial sectors show some differences in experiencing pressures or being motivated by drivers. Research limitations/implications – The main limitations to this paper are the relatively small sample of SMEs and the potentially overlooked variables. Practical implications – Chinese manufacturing SMEs and their larger customers, as well as governments, are likely to obtain some implications from this study if they are willing to consider any GSCM initiatives throughout the supply chain. Originality/value – The paper clearly explores the GSCM pressures and drivers faced by the Chinese manufacturing SMEs where the results may differ from the findings through the studies on large enterprises or SMEs in other national context.